Model Pemerolehan Bahasa Arab Sebagai Bahasa Asing Pada Peserta Didik Non-Native Speaker (Kajian Teori Psikolinguistik) - Nafiul Huda (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2018)
The language acquisition model of a person is one of the most interesting themes to be discussed. Especially the process of obtaining foreign languages, because in addition to the concept of acquisition of the first language in children, also has a linkage, between the process of learning the language to the acquisition of foreign languages. Of course there is a difference between the process of language learning with the process of language acquisition, especially foreign languages. At least the process of acquisition of language can be seen from two sides, namely from the side of the process of obtaining a foreign language in the frame of psycholinguistics and from the side of the process of obtaining foreign languages in the sociolinguistic framework, or in its development can also be seen in the neurolinguistic side that examines the nervous system in the human brain to the process of acquisition foreign language.